Vitamin D status of black and white Americans and changes in vitamin D metabolites after varied doses of vitamin D supplementation,. Issue 1 (18th May 2016) - Alzaman, Naweed S; Dawson-Hughes, Bess; Nelson, Jason; D'Alessio, David; Pittas, Anastassios G
ABSTRACT: Background : Controversy exists over the disparate circulating 25-hydroxyvitamin D [25(OH)D] concentrations between black and white Americans. Objective: We sought to determine whether there are differences in total and directly measured free 25(OH)D concentrations between black and white American adults and how daily supplementation with cholecalciferol changes these concentrations. Design: Cross-sectional and longitudinal analyses were conducted with the use of data from 2 placebo-controlled, randomized trials at 2 academic medical centers in the United States: CaDDM (Calcium and Vitamin D in Type 2 Diabetes) and DDM2 (Vitamin D for Established Type 2 Diabetes). A total of 208 subjects with pre- or well-controlled diabetes with a mean age of 59.1 y and mean body mass index (BMI; in kg/m 2 ) of 31.6 were randomly assigned to receive daily cholecalciferol supplementation at 1 of 2 doses (2000 or 4000 IU) or a matching placebo for 16 wk. We measured serum total 25(OH)D, vitamin D–binding protein (DBP) by 2 different immunoassays (with the use of monoclonal or polyclonal antibodies), parathyroid hormone, and albumin. Free 25(OH)D concentration was directly measured and calculated. Results: Blacks had lower total 25(OH)D concentrations than whites [adjusted median: 20.3 ng/mL (95% CI: 16.2, 24.5 ng/mL) compared with 26.7 ng/mL (95% CI: 25.2, 28.1 ng/mL), respectively; P = 0.026)], and a higher proportion of blacks had total 25(OH)D concentrations <20 ng/mL (46% compared with 19%, respectively; P < 0.001). Directly measured free 25(OH)D concentrations were lower in blacks than in whites [adjusted median: 4.5 ng/mL (95% CI: 3.7, 5.4 ng/mL) compared with 5.7 ng/mL (95% CI: 5.4, 5.9 ng/mL), respectively; P = 0.044] and were strongly correlated with total 25(OH)D without an effect of race. DBP was lower in blacks when measured by the monoclonal but not the polyclonal antibody immunoassay. Cholecalciferol supplementation increased total and measured free 25(OH)D concentrations proportionally to the dose and without a difference between races. Conclusions: The relation between free and total 25(OH)D did not vary systematically by race in this multiracial population with pre- or well-controlled diabetes. The results need to be replicated in additional cohorts before concluding that the clinical assessment of vitamin D status in blacks and whites should follow a single standard. The CaDDM and DDM2 trials were registered at clinicaltrials.gov as NCT00436475 and NCT01736865, respectively.